2021
DOI: 10.4103/2221-1691.321130
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activity and inhibition against Staphylococcus aureus NorA efflux pump by ferulic acid and its esterified derivatives

Abstract: Objective: To evaluate the inhibitory activity of ferulic acid and four of its esterified derivatives (methyl, ethyl, propyl, and butyl) against resistance mechanisms in Staphylococcus aureus strains. Methods: Ferulic acid derivatives were obtained by esterification with methanol, ethanol, propanol, and butanol, and then characterized by hydrogen and carbon-13 nuclear magnetic resonance analysis. The minimum inhibitory concentrations (MIC) of ferulic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…The efflux pump inhibition was assayed using a subinhibitory concentration of efflux pump standard inhibitors and tannic acid (MIC/8), observing their capacity to decrease the MIC of ethidium bromide and antibiotics due the possible inhibitory effect of these substances. In other studies, the effectiveness of inhibiting the efflux pump mechanism was also demonstrated in Staphylococcus aureus strains by caffeic and gallic acid (the MrsA pumps of the strain RN-4220 and NorA of the strain 1199B) [73], hydroxyamines derived from lapachol and norlachol (NorA pumps from the strain 1199B) [74], ferulic acid and its esterified derivatives (NorA pumps from the strain 1199B) [75]. In contrast, studies [76] have shown the activity of blocking the efflux pump by quercetin.…”
Section: Antibacterial Activity Of the Habh And Cuhabh Complexesmentioning
confidence: 79%
“…The efflux pump inhibition was assayed using a subinhibitory concentration of efflux pump standard inhibitors and tannic acid (MIC/8), observing their capacity to decrease the MIC of ethidium bromide and antibiotics due the possible inhibitory effect of these substances. In other studies, the effectiveness of inhibiting the efflux pump mechanism was also demonstrated in Staphylococcus aureus strains by caffeic and gallic acid (the MrsA pumps of the strain RN-4220 and NorA of the strain 1199B) [73], hydroxyamines derived from lapachol and norlachol (NorA pumps from the strain 1199B) [74], ferulic acid and its esterified derivatives (NorA pumps from the strain 1199B) [75]. In contrast, studies [76] have shown the activity of blocking the efflux pump by quercetin.…”
Section: Antibacterial Activity Of the Habh And Cuhabh Complexesmentioning
confidence: 79%
“…Thus, it is not surprising that many efforts have been devoted to the development of FA derivatives [ 21 , 27 , 29 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 ]. Some of their relevant structural modifications and properties are summarized in Table 1 .…”
Section: Introductionmentioning
confidence: 99%
“…Various phytocompounds have been studied for its ability to inhibit S. aureus efflux pumps, including terpenes such as eugenol [17], carvacrol, thymol [18], estragole [19], α-pinene, and limonene [20]. Inhibition of NorA has also been reported for ferulic acid and its esterified derivatives [21], chalcones [22], and vitamin K3 [23]. On the other hand, various synthetic EPIs have been reported as efflux pump inhibitors [24][25][26].…”
Section: Introductionmentioning
confidence: 99%